Kearifan Lokal pada Konstruksi Rumah Adat Kampung Bena dalam Mendukung Pengembangan Wisata Budaya Berkelanjutan - Paulus Nong Wisang; Natalia Kristiani Tandafatu; Rosalina Andriyani E. Pareira (PERSPEKTIF, 2026)
Bena Village in Ngada Regency, Flores, East Nusa Tenggara, is one of the traditional settlements that has preserved the authenticity of its traditional houses (sa'o) and the local wisdom values that have been passed down from generation to generation. These values not only reflect the cultural identity of the local community but also have the potential to support the development of sustainable cultural tourism. This study aims to identify and analyze the local wisdom embodied in the construction of traditional houses in Bena Village and to examine its contribution to supporting sustainable cultural tourism development. The study employed a qualitative approach using an ethnographic method. Data were collected through observation, in-depth interviews, and documentation, and were analyzed descriptively to understand the meanings and practices of local wisdom embedded in the construction of traditional houses (sa'o). The findings reveal that the local wisdom embedded in the construction of traditional houses in Bena Village encompasses ecological aspects through the use of local materials and adaptation to climatic conditions; structural and technical aspects through earthquake-resistant construction systems and the use of traditional joints; socio-cultural aspects through spatial symbolism, mutual cooperation values, and intergenerational transmission of knowledge; and economic aspects through the utilization of traditional houses as attractions for cultural tourism. These values contribute to the preservation of cultural heritage while strengthening the attractiveness of the destination in a sustainable manner. The study implies that the local wisdom embedded in the construction of traditional houses in Bena Village has high relevance to the development of sustainable cultural tourism. The principles embodied therein can serve as a foundation for cultural heritage preservation, the strengthening of local identity, and tourism development oriented toward environmental, social, and economic sustainability.